Cephalad–caudad versus transverse blunt expansion of the low transverse uterine incision during cesarean delivery. (July 2016) - Xodo, Serena; Saccone, Gabriele; Cromi, Antonella; Ozcan, Pinar; Spagnolo, Emanuela; Berghella, Vincenzo
Abstract: It is imperative to have evidence-based guidelines for cesarean delivery. The aim of this meta-analysis was to evaluate the effectiveness of a cephalad–caudad compared to transverse blunt expansion of the uterine incision to reduce blood loss in women who underwent low-segment transverse cesarean delivery. We therefore performed a systematic search in electronic databases from their inception until March 2016. We included all randomized trials comparing cephalad–caudad versus transverse (control group) blunt expansion of the uterine incision in women who underwent a low transverse cesarean delivery. The primary outcome was postpartum blood loss, defined as the mean amount of blood loss (mL). Two trials (921 women) were analyzed. After the transverse uterine incision in the lower uterine segment with the scalpel, the uterine incision was then bluntly expanded by the designated method. Blunt expansion of the primary incision was derived by placing the index fingers of the operating surgeon into the incision and pulling the fingers apart laterally (transverse group) or cephalad (cephalad–caudad group). Women who were randomized in the cephalad–caudad group had lower: mean of postpartum blood loss, hemoglobin drop and hematocrit drop 24 h after cesarean, unintended extension, uterine vessels injury, blood loss >1500 mL and need for additional stitches. There was no statistically significant difference in the incidence of blood loss >1000 mL, in the operating time and in post-operative pain. In conclusion, expansion of the uterine incision with fingers in a cephalad–caudad direction is associated with better maternal outcomes and, therefore, should be preferred to transverse expansion during a cesarean delivery.